2013
DOI: 10.1097/mpg.0b013e31827af200
|View full text |Cite
|
Sign up to set email alerts
|

Response to Hepatitis A and B Vaccination in Pediatric Patients With Celiac Disease

Abstract: The rate of seroconversion to the hepatitis B virus- and HAV vaccine is lower in patients with CD than in healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Therefore, we included 17 randomized clinical trials in the qualitative synthesis. [6][7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26] Three studies were further excluded because they lacked a control arm; 17-19 2 other studies, reporting both a retrospective and a prospective cohort of patients, were considered only for the retrospective design, since the prospective cohort lacked a control arm. 20,21 As a result, 14 studies were considered for the metaanalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we included 17 randomized clinical trials in the qualitative synthesis. [6][7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26] Three studies were further excluded because they lacked a control arm; 17-19 2 other studies, reporting both a retrospective and a prospective cohort of patients, were considered only for the retrospective design, since the prospective cohort lacked a control arm. 20,21 As a result, 14 studies were considered for the metaanalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the immunologic response would not appear to be affected by the natural history of CD[17]. Urgancy and Kalyoncu[18] determined the response rate to hepatitis A (HAV) and HBV vaccination, persistence of protection against HAV and HBV, and the occurrence of acute HAV or HBV infections during a period of follow-up in 30 children affected by CD in comparison with 50 healthy controls matched for age, sex, and body mass index[18]. They found natural immunity for HAV in 14 (46%) out 30 CD patients and 15 (30%) of the 50 controls, whereas none of the patients and controls showed evidence of earlier exposure to HBV.…”
Section: Responses To Vaccinations In Children With Celiac Diseasementioning
confidence: 99%
“…HLA-DQ2 haplotype may be responsible for lack of induction of the Th2 response that is necessary for B cell differentiation and formation of memory B cells. Other authors have suggested that the response to HBV vaccination in individuals affected by CD may depend on disease activity and compliance to a gluten free diet (GFD)[12,13,15,18]. Indeed, gluten consumption at the time of vaccination has been hypothesized as a cause of failure of immunity.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of CD subjects to respond to HBV vaccination has great importance for public health policies as the nonresponders could be regarded as a reservoir for HBV [20]. The studies that have addressed the relation between CD and HBV vaccination in children are summarized in Table 1 [21][22][23][24][25][26][27][28][29]. In the earliest report involving 26 celiac patients aged 9.2 ± 4.6 years and 18 age-matched controls, receiving the full complement of childhood vaccination (HBV, tetanus, rubella, Haemophilus inluenzae type b), Park et al [21] demonstrated that a signiicantly higher proportion of subjects in the CD group failed to respond to HBV vaccine compared with controls (53.9% versus 11.1%; p < 0.05).…”
Section: Responses To Vaccinations In Celiac Childrenmentioning
confidence: 99%
“…Thus, the immunologic response did not seem to be inluenced by the natural history of CD [27]. Urganci and Kalyoncu determined the rate of response to hepatitis A (HBA) and HBV vaccine, the duration of protection against HAV and HBV, and the incidence of acute HAV or HBV infections during follow-up in 30 pediatric patients with CD and compared them with 50 healthy age-, sex-, and body mass index-matched controls [28]. They found that 14 (46%) of 30 CD patients and 15 (30%) of the controls had natural immunity for HAV, whereas all patients and controls did not show evidence of earlier exposure to HBV.…”
Section: Responses To Vaccinations In Celiac Childrenmentioning
confidence: 99%